Platelet‐rich plasma in treatment of scar, atrophy, and sulcus: Short‐ and long‐term results - Peak Woo (Laryngoscope Investigative Otolaryngology, 2023)
Abstract Objective Platelet‐rich plasma (PRP) is rich in growth factors and is easily obtained from blood samples. Long‐term data after PRP injection into the larynx should be improved. This study reports the short‐term (3 months) and long‐term (12 months) voice results after PRP injection. Materials and Methods Sixty‐three patients with scars (n = 34), sulcus vocalis (n = 17), recalcitrant nodules (n = 5), atrophy (n = 4), or a combination of these (n = 3) were included (158 injections; median follow‐up = 12.3 months). Stroboscopy, voice handicap index (VHI‐10), and cepstral spectral index of dysphonia (CSID) before and after treatment (3 months) and at 12 months were tabulated. Results VHI‐10 changed from 19.5 to 14 at 3 months and 21 to 15 in the long term. The CSID scores improved from 31 to 21 in the short term and 31 to 26 in the long term (p < 0.001, paired t‐test). Patients reported improved vocal effort and stamina with slight VHI or CSID score changes. Stroboscopy revealed improved closure and mucosal waves. Patients with severe dysphonia were less likely to improve compared to those with mild to moderate dysphonia. Some patients showed short‐term improvements and then deteriorated back to baseline CSID over time (p < .05, paired t‐test). Conclusion Both short‐ and long‐term improvements in voice following PRP injection have been reported. Patients with mild‐to‐moderate dysphonia had better outcomes. PRP injection is an alternative treatment for patients with mild‐to‐moderate dysphonia due to vocal fold scarring, sulcus, and atrophy. Level of evidence II Prospective case series treatment.